Taxonomy and distribution of Abrawayaomys (Rodentia: Cricetidae), an Atlantic Forest endemic with the description of a new species - Pardiñas, Ulyses F. J.; Teta, Pablo; D’elía, Guillermo (Zootaxa, 2009)
Abrawayaomys is a monotypic sylvan cricetid genus that stands out within the sigmodontine radiation due to its spiny pelage associated with unusual craniodental morphology. We made a reappraisal of its knowledge throughout the known distribution, critically addressing their geographic distribution in Argentina (four recording localities restricted to the province of Misiones) and providing a detailed morphological analysis of one trapped individual from Iguazú area; this, plus an examination of other available specimens and literature data permits to produce an emended diagnosis for the genus. Comparisons among the few known specimens from Argentina and Brazil highlighted several differences in measurements as well as in craniodental and external morphology, allowing the description of a new species and suggesting the potential existence of another still undescribed form for the Brazilian populations of Minas Gerais. This new alpha-taxonomy scenario is preliminary correlated to the main geomorphological features that characterize southeastern Brazil. The phylogenetic position of Abrawayaomys, historically assigned to Thomasomyini or considered as a sigmodontine incertae sedis, is discussed in the light of the traits described here. Based on this new evidence, we suggest assigning Abrawayaomys to Thomasomyini, although similarities (here regarded as convergences) with members of Akodontini are highlighted.